2007
DOI: 10.1007/s00253-007-1141-3
|View full text |Cite
|
Sign up to set email alerts
|

Purification and biochemical characterization of a transglucosilating β-glucosidase of Stachybotrys strain

Abstract: The filamentous fungus Stachybotrys sp has been shown to possess a rich beta-glucosidase system composed of five beta-glucosidases. One of them was already purified to homogeneity and characterized. In this work, a second beta-glucosidase was purified and characterized. The filamentous fungal A19 strain was fed-batch cultivated on cellulose, and its extracellular cellulases (mainly beta-glucosidases) were analyzed. The purified enzyme is a monomeric protein of 78 kDa molecular weight and exhibits optimal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
2
24
0
2
Order By: Relevance
“…3 (the gel image on the left), there are at least two components in each type of glycoside hydrolase in the extracellular crude samples of the four filamentous fungi. These results are consistent with the previous reports [39][40][41]. Thus, when the native electrophoresis is carried out with the same amount of sample analyzed under the same conditions, and the postelectrophoresis gel strips are soaked simultaneously in the same substrate solution corresponding to each enzyme at different pHs, the changes in concentration of the substrate or product (reflected by each band's gray values) are expected to be indicators of the pH dependence of the corresponding enzyme component, as the gray values were in positive linear correlation with relative enzyme activities.…”
Section: Quantitative Analysis Of the Ph Profile Of Each Component Insupporting
confidence: 96%
“…3 (the gel image on the left), there are at least two components in each type of glycoside hydrolase in the extracellular crude samples of the four filamentous fungi. These results are consistent with the previous reports [39][40][41]. Thus, when the native electrophoresis is carried out with the same amount of sample analyzed under the same conditions, and the postelectrophoresis gel strips are soaked simultaneously in the same substrate solution corresponding to each enzyme at different pHs, the changes in concentration of the substrate or product (reflected by each band's gray values) are expected to be indicators of the pH dependence of the corresponding enzyme component, as the gray values were in positive linear correlation with relative enzyme activities.…”
Section: Quantitative Analysis Of the Ph Profile Of Each Component Insupporting
confidence: 96%
“…9), indicating that Unbgl1A possesses a transglucosylation activity that transfers a glucose unit to the receptor sugar (in this case, it is cellobiose). This result is consistent with the reported enzymes from Stachybotrys microbispora and zygomycete R. miehei [18,21]. Krisch and other groups showed that after 35% (350 mg/ml) cellobiose was mixed with b-glucosidases for 72 h, there was 86 mg/ml cellotriose generated [18,21,22].…”
Section: Transglucosylationsupporting
confidence: 82%
“…The reaction procedure was modified in our laboratory by Saibi et al (2007). One unit of enzymatic activity is the amount of enzyme required to release 1 lmol p-nitrophenol per min.…”
Section: Pectinolytic Cellulasic and Xylolytic Activities Assaysmentioning
confidence: 99%